Development of cereal bar with baru almonds and pineaplle peels (Research, Society and Development, 2021)
Cereal bars have gained constantly growing interests because of their nutritional quality and practicality in consumption. To meet the increasing market needs, their formulation strategies are evolving with each passing day. Therefore, the present study aimed to develop a new formulation of cereal bars with baru almonds and pineapple peels, an agricultural waste, added in different quantities, or be 5.5% F1, 8.5% F2, and 9.5% F3. The developed bars were characterised for microbiological quality, sensory acceptability, and physico-chemical properties. The microbiological analysis identifying